Textual Imitation: Making and Seeing in Literature - Hart, J. author. aut Link
XIV, 158 p. 1 illus.
Keywords: Textual Imitation offers a new critique of the space between fiction and truth, poetry and philosophy. In a nimble, yet startlingly wide-ranging argument, esteemed scholar Jonathan Hart argues that recognition and misrecognition are the keys to understanding texts and contexts from the Old World to the New World.